(untitled) - Yadav, S. K. (Darya Ganj, New Delhi, 2004)
Contents of material: 1/Impact of technology transformations in libraries. 2/ Computer technology in libraries. 3/ Library automation. 4/ Online cataloguing. 5/ Technical services. 6/ Trends of library networking. 7/ Information security.
Keywords: Cataloging,Computer networks